A review: MA in Art Education online at Boston University. Issue 3 (6th December 2012) - Simpson, Judith
Distance education has become a preferred method of learning by many educators wishing to gain professional degrees. While the reasons for this phenomenon are understandable, there is still a perception among some that online degrees are diluted in scope, content and rigour. That perception drove the Art Education Department at Boston University to maintain the level of integrity in all areas that exists in our campus programme when designing an online degree.